Sudan Load Forecast for Period 2017 – 2066 Using Seasonal Time Series Model (University of Khartoum Engineering Journal, 2022)
The importance of this paper is the use of seasonal time series models (some seasonal models of Box & Jenkins) to predict electricity consumption in Sudan National Grid, making it easier to estimate consumption, and provide accurate indicators for planners to develop appropriate future plans in electricity sector. The objective of this paper is to forecast the electric load consumption using different model.